Hongkongmyces wuhanensis sp. nov. from freshwater habitats in Wuhan, China - Shu, Yong-Xin; Hyde, Kevin D.; Al-Otibi, Fatimah O.; Doilom, Mingkwan; Kitiphong, Khongphinitbunjong; Dong, Wei (Phytotaxa, 2025)
Hongkongmyces is a genus of particular interest, as its type species was isolated from a biopsy specimen of a patient with an invasive foot infection, making it the only member of Lindgomycetaceae associated with human infections. However, most Hongkongmyces species have been identified as saprobes from freshwater habitats. During our ongoing investigation into the taxonomy and diversity of freshwater fungi in southern China and along a north-south gradient, we discovered a novel species, Hongkongmyces wuhanensis, from a freshwater lake in Wuhan City, China. The classification of the new species is supported by morphological characteristics and multi-locus phylogeny using combined LSU, SSU, ITS and tef1-α rDNA sequence data. Hongkongmyces wuhanensis is distinguished by its narrowly fusiform or vermiform, yellowish brown, mostly 5-septate ascospores. A detailed description, illustration, and an updated phylogenetic tree are presented. In addition, we discuss the possibility of Clohesyomyces being the asexual morph of Aquimassariosphaeria.